1998
DOI: 10.1021/bi981820f
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Kinetic and Chemical Mechanism of Malic Enzyme Using (2R,3R)-erythro-Fluoromalate as a Slow Alternate Substrate

Abstract: (2R,3R)-erythro-Fluoromalate, but not the threo isomer, is a slow substrate for chicken liver malic enzyme with either NADP or 3-acetylpyridine-NADP (APADP) as the other substrate. The Km for erythro-fluoromalate is similar to that of malate, but the turnover number with NADP is 3300-fold slower, although 5.5-fold faster with APADP than with NADP. Deuteration of fluoromalate at C-2 gave an isotope effect on V/K of 1.39 with NADP and 3.32 with APADP. With NADP, the 13C isotope effects at C-4 were 1.0490 with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Catalysis by MEs generally proceeds in two steps -the dehydrogenation of malate to produce oxaloacetate (the same reaction as that catalyzed by MDH), and decarboxylation to produce pyruvate [5]. A general base is needed for the first step to extract the proton for dehydrogenation, and a general acid is needed for the second step to protonate the product of decarboxylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysis by MEs generally proceeds in two steps -the dehydrogenation of malate to produce oxaloacetate (the same reaction as that catalyzed by MDH), and decarboxylation to produce pyruvate [5]. A general base is needed for the first step to extract the proton for dehydrogenation, and a general acid is needed for the second step to protonate the product of decarboxylation.…”
Section: Discussionmentioning
confidence: 99%
“…Malic enzyme (ME; EC 1.1.1.40) catalyzes the oxidative decarboxylation of L-malate to pyruvate with the concomitant reduction of the cofactor NAD + or NADP + [1][2][3][4][5]. In addition to NAD(P) + , the enzyme also requires divalent cations (Mg 2+ or Mn 2+ ) as cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…4). Interestingly, Jeff Urbauer showed that with erythrofluoromalate and acetylpyridine-NADP the mechanism remained stepwise, because the fluorine substitution decreases the equilibrium constant for the reaction by an order of magnitude (41).…”
Section: Reflections: Use Of Isotope Effectsmentioning
confidence: 99%
“…The expected effects of hyperconjugation in the oxaloacetate intermediate were, however, seen with the slow alternate substrate (2R,3R)-erythro-fluoromalate. 11 This substrate has a turnover number decreased by a factor of 3300, so the chemistry is certainly rate limiting. Deuteration of fluoromalate at C-2 gave a V/K isotope effect of 1.39 with NADP and 3.32 with acetypyridine-NADP.…”
Section: Multiple Isotope Effect Methodsmentioning
confidence: 99%